Yeha and Hawelti: cultural contacts between Sabaʾ and DʿMT — New research by the German Archaeological Institute in Ethiopia - Japp, Sarah; Gerlach, Iris; Hitgen , Holger; Schnelle, Mike (Proceedings of the Seminar for Arabian Studies, 2011)
In 2009 the Sanaa Branch of the Orient Department of the German Archaeological Institute (DAI) started research work in the two Ethio-Sabaean sites of Yeha and Hawelti in northern Ethiopia, both situated in the highlands of Tigray. Yeha is famous for its well-preserved Great Temple regarded as a holy place and national monument, and which displays a distinct South Arabian style. A second ancient monumental building is also known to have been erected in a timber framework system with direct similarities to a Sabaean building in Ṣirwāḥ (Yemen) from the ninth century BC. An ancient necropolis as well as another temple were also found and partly excavated. Relics from ancient material culture such as pottery, terracotta figurines, and inscriptions were examined. In Hawelti new investigation of the field of stone stelae was undertaken. Some were excavated apart from two cultic buildings in the 1950s. They can now be compared with South Arabian pillars in terms of form, stonemasonry, and incised Sabaean letters. The DAI investigations have strengthened the supposition that South Arabian influence at both sites is not only visible in specific architectural components but also in several other aspects of material culture. The extent of this influence seems to indicate the presence of Sabaean settlers in northern Ethiopia and south-eastern Eritrea from the early first millennium BC onwards. As well as elements of the culture, religion, and political system of Saba, the Ethio-Sabaean kingdom of DʿMT in the Abyssinian highlands also included traditional indigenous elements and moreover, it shows a novel combination of pointing to an acculturation process between the two different population groups and their respective cultures.